Potency of Peripheral Blood- and Umbilical Cord Blood-derived Dendritic Cells and Their Secretomes as Vaccines for Cancer - Haifa, Rima; Sartika, Cynthia Retna; Faried, Ahmad; Hadisaputri, Yuni Elsa; Chouw, Angliana; Wijaya, Andi; Barliana, Melisa Intan (Molecular and Cellular Biomedical Sciences, 2024)
Dendritic cell (DC) vaccines, as immunotherapy agents, can gather up and transport cancer-related antigens to T lymphocytes, activating anti-tumor effector responses. After being activated by DC, cytotoxic T lymphocyte cells (CTL) will secrete the cytolytic granzyme B that can effectively induce rapid apoptosis of target cells. On the other hand, DC also secrete several cytokines and a large number of exosomes, which together operate as a whole antigen-presenting entity. The efficacy of the vaccine’s treatment may be affected by the sources used for DC vaccines. Umbilical cord blood (UCB) from healthy donors can be employed when autologous cancer patient’s peripheral blood (PB) cannot be used as a source for isolating DC due to genetic abnormalities. Comparing UCB to other sources, there is a painless method of collecting sources as opposed to PB, which necessitates a venipuncture or leukapheresis procedure to isolate the blood. Many studies related to the use of PB-DC have been carried out, but research on potential comparisons between PB-DC and UCB-DC is still very limited. In this review, the potential of PB- and UCB-derived DC and their secretomes for cancer will be discussed.Keywords: dendritic cells, vaccines, umbilical cord blood, peripheral blood